Whole‐exome sequencing improves mutation detection in a diagnostic epidermolysis bullosa laboratory. (19th November 2014) - Takeichi, T.; Liu, L.; Fong, K.; Ozoemena, L.; McMillan, J.R.; Salam, A.; Campbell, P.; Akiyama, M.; Mellerio, J.E.; McLean, W.H.I.; Simpson, M.A.; McGrath, J.A.
Summary Background Subtypes of inherited epidermolysis bullosa (EB) vary significantly in their clinical presentation and prognosis. Establishing an accurate diagnosis is important for genetic counselling and patient management. Current approaches in EB diagnostics involve skin biopsy for immunohistochemistry and transmission electron microscopy, and Sanger sequencing of candidate genes. Although informative in most cases, this approach can be expensive and laborious and may fail to identify pathogenic mutations in 15% of cases. Objectives Next‐generation DNA sequencing (NGS) technologies offer a fast and efficient complementary diagnostic strategy, but the value of NGS in EB diagnostics has yet to be explored. The aim of this study was to undertake whole‐exome sequencing (WES) in nine cases of EB in which established diagnostic methods failed to make a genetic diagnosis. Methods Whole‐exome capture was performed using genomic DNA from each case of EB, followed by massively parallel sequencing. Resulting reads were mapped to the human genome reference hg19. Potentially pathogenic mutations were subsequently confirmed by Sanger sequencing. Results Analysis of WES data disclosed biallelic pathogenic mutations in each case, with all mutations occurring in known EB genes (LAMB3, PLEC, FERMT1 and COL7A1). This study demonstrates that NGS can improve diagnostic sensitivity in EB compared with current laboratory practice. Conclusions With appropriate diagnostic platforms and bioinformatics support, WES is likely to increase mutation detection in cases of EB and improve EB diagnostic services, although skin biopsy remains an important diagnostic investigation in current clinical practice.